2010
DOI: 10.1677/joe-09-0345
|View full text |Cite
|
Sign up to set email alerts
|

Metformin suppresses hepatic gluconeogenesis through induction of SIRT1 and GCN5

Abstract: Abnormal elevation of hepatic gluconeogenesis is central to the onset of hyperglycaemia in patients with type 2 diabetes mellitus (T2DM). Metformin corrects hyperglycaemia through inhibition of gluconeogenesis, but its mechanism of action is yet to be fully described. SIRT1 and GCN5 (listed as KAT2A in the MGI Database) have recently been identified as regulators of gluconeogenic gene expression through modulation of levels and activity of the coactivators cAMP-response element binding protein-regulated transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
139
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(148 citation statements)
references
References 48 publications
7
139
0
2
Order By: Relevance
“…TORC2 protein levels were reduced, gene expression and activation of the PGC1-alpha target gene PEPCK was decreased, and plasma glucose and insulin levels were lower. The data suggested the induction of hepatic GCN5 as a potential therapeutic strategy for treatment of type 2 diabetes [83].…”
Section: Gcn5 and Pcafmentioning
confidence: 96%
“…TORC2 protein levels were reduced, gene expression and activation of the PGC1-alpha target gene PEPCK was decreased, and plasma glucose and insulin levels were lower. The data suggested the induction of hepatic GCN5 as a potential therapeutic strategy for treatment of type 2 diabetes [83].…”
Section: Gcn5 and Pcafmentioning
confidence: 96%
“…The studies with unknown status are not reported in the particular, metformin upregulates SIRT1, which, in turn, reduces TORC2 and PGC1-a activity and the plasma levels of glucose and insulin. 94 A 16-week double-blind, placebo-controlled, completed, and published study (NCT00570739) demonstrated that the combination therapy with metformin plus colesevelam (a bile acid sequestrant) was able to significantly reduce the concentration of low-density lipoprotein (LDL) particles and improved the atherogenic plasma lipoprotein profile of patients with early T2DM (Table 2). 95 The dietary polyphenol resveratrol (one of the first activators of SIRT1 to be identified) exerts an anti-diabetic activity by regulating the activity of AMPK and PGC1a.…”
Section: Nct02046395mentioning
confidence: 99%
“…A recent study reported that GCN5 expression in the liver was induced by the drug metformin (29). Metformin is used in diabetes to improve insulin sensitivity and inhibit gluconeogenesis.…”
Section: Discussionmentioning
confidence: 99%